Disclosure of climate change risk in credit ratings: An analytical framework to perform a status-quo assessment of the disclosure of climate change risks in rating methodologies and ratings reports by selected credit rating agencies - Miriam Breitenstein; Stefania Ciummo; Florian Walch (European Central Bank (ECB), 2022)
Climate change can be a source of financial risk. This paper examines how credit rating agencies accepted by the Eurosystem incorporate climate change risk in their credit ratings. It also analyses how rating agencies disclose their assessments of climate change risks to rating users. The paper develops an analytical framework to compare the agencies' definitions, methodologies, assessment models, data usage and disclosure practices. The paper reveals large differences in methodologies and disclosure practices across rating agencies and asset classes. The authors identify three main areas for improvement with respect to climate-related disclosures. These areas concern the level of granularity of definitions of climate change risk, the transparency around models and methods used to estimate the exposure to climate change risk and the disclosure of the magnitude of the impact of material climate change risk on credit ratings.
Keywords: E52; E58; G24; G32; Q54; 330; climate change; monetary policy; risk management; credit risk; creditrating agencies